The Effects of Dapagliflozin Therapy on Serum Uric Acid Levels in Patients of Type 2 Diabetes Mellitus with Hyperuricemia - Mariam, Ezza; Qureshi, Muhammad Naeem; Siddiqi, Fuad Ahmad; Hassan, Fayyaz; Siddiqi, Kanaz Ahmad; Yaseen, Laila (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the impact of Dapagliflozin on Serum Uric Acid levels in patients of Type-2 Diabetes Mellitus having hyperuricemia. Study Design: Quasi-Experimental Study. Place and Duration of Study: Medicine Department of Tertiary Care Hospital Rawalpindi, Pakistan, from Sep 2023 to Sep 2024. Methodology: In this study, participants were categorized into two different groups. Individuals in Group-A received Dapagliflozin 10 mg/d in conjunction with their standard glucose-lowering medications, while those in Group-B proceeded with regular glucose-lowering medications. Baseline physical examinations, as well as blood samples, were collected from all the subjects of both groups, and then these were performed again after the 12, 24, as well as 48 weeks of treatment. Results: A total of 250 participants were enrolled in this study. Our study results indicate that after 48 weeks, the mean serum Uric Acid level decreased significantly by 28.0µmol/L in Group-A, while there was no change in Group-B (0.0 µmol/L), which was statistically significant (p<0.001). For HbA1c levels, the Group-A had a mean reduction of 1.40%, compared to a 1.46% reduction in the glucose-lowering medications group, which was not significant (p=0.47). Conclusion: Dapagliflozin reduced serum Uric Acid levels in Type 2 Diabetes Mellitus patients with hyperuricemia as opposed to glucose-lowering medication alone.